A SPATIALLY-STRUCTURED THREE-SPECIES MODEL SYSTEM FOR BENTHIC COMMUNITY - M. Saleem et al. (Proceedings of ICMSA, 2005)
Recently Donalson et al [3] gave a one-prey (mussel) and one-predator(sea star) model-system representing the spatially-structured dynamics ofbenthic community. We generalize this model in this paper and extend itsscope to the dynamics of three species of benthic community namely:mussel, sea star and spiny lobster.Keywords: Spatially-structured; Benthic species; Predator preyinteractions